2004
DOI: 10.1007/s00467-004-1460-x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cardiovascular disease in adults who have had childhood nephrotic syndrome

Abstract: While increased risk of cardiovascular disease (CVD) in patients with hyperlipidemia, chronic kidney disease (CKD), or end-stage renal disease (ESRD) is well documented, transient hyperlipidemia or intermittent renal disease as a consequence of relapsing nephrotic syndrome (NS) has not been studied. To investigate this enigma, 62 patients, between 25 and 53 years of age, who had steroid-responsive/dependent NS during childhood, were identified from the records of the Division of Pediatric Nephrology at Yale Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 15 publications
4
27
0
Order By: Relevance
“…In opposition, despite the above lipoprotein changes, Lechner et al [24] have not shown a consistent relationship between NS, in the absence of uremia, and an increased risk of CVD.…”
Section: Nephrotic Syndromementioning
confidence: 93%
“…In opposition, despite the above lipoprotein changes, Lechner et al [24] have not shown a consistent relationship between NS, in the absence of uremia, and an increased risk of CVD.…”
Section: Nephrotic Syndromementioning
confidence: 93%
“…One study of 40 adults who had relapsing NS as children did not show a higher incidence of cardiovascular disease, implying that longterm cardiovascular risk was not increased by intermittent hyperlipidemia during nephrotic relapses in childhood, although this study was small and no firm conclusion can be derived from the data. 89 The use of renin-angiotensin-aldosterone blockers and statins may be considered on a case-by-case basis in MCD adults, particularly those patients with hypertension.…”
Section: Nonimmunomodulatory Therapies For MCDmentioning
confidence: 99%
“…However, in children, the role of idiopathic nephrotic syndrome (INS) in the development of atherosclerosis has been unclear [4]. INS is associated with the presence of several classical risk factors for cardiovascular disease, including obesity, hypercholesterolemia, increased thrombinogenesis, impaired fibrinolysis, enhanced platelet activation, oxidative stress, insulin resistance, immunological dysregulation and subclinical inflammation [5, 6].…”
Section: Introductionmentioning
confidence: 99%